The Role Of Knowledge Management In The Development Of The Educational Process - bourouis, adel; addel, ghazali (El Omda in Linguistics and Discourse Analysis, 2023)
In this research paper, we will discuss the role that knowledge management plays in the development process of the educational process as an educational program and educational system, through the results of knowledge management and its implications for the educational process and how it helps to improve its quality and product training and as an effective tool when the intersection between the requirements of knowledge management and components of the educational process as a policy of the educational system.